2019
DOI: 10.1002/nop2.406
|View full text |Cite
|
Sign up to set email alerts
|

Pain, fatigue, anxiety and depression in older home‐dwelling people with cancer

Abstract: AimGlobally, cancer incidence counts for more than 14 million cases and the number increases with age. The aim of this study was to investigate the occurrence of pain, fatigue, anxiety and depression in association with demographic and clinical factors.DesignA cross‐sectional descriptive design was used.MethodsWe performed descriptive statistics to analyse the questionnaires completed from 174 older home‐dwelling people with cancer.ResultsThe people with cancer reported low occurrence of pain, fatigue, anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 57 publications
3
22
0
Order By: Relevance
“…Huang et al [23] revealed dependence in ADL and presence of depression as significant independent factors associated with increased odds of reporting falls and balance/walking difficulty in the past 12 months for all cancer types; however, they did not examine personality. Corresponding to Huang et al [23], our findings with falls implying health care, presence of somatic comorbidity, and no performance of physical activity indicate a sample of frail and fatigued OCSs, also described characteristics for this target group in previous studies [19,36]. The high prevalence of frailty in OCSs might lead to concerns and further to their poor life satisfaction experience.…”
Section: New Findings and Their Meaningsupporting
confidence: 80%
“…Huang et al [23] revealed dependence in ADL and presence of depression as significant independent factors associated with increased odds of reporting falls and balance/walking difficulty in the past 12 months for all cancer types; however, they did not examine personality. Corresponding to Huang et al [23], our findings with falls implying health care, presence of somatic comorbidity, and no performance of physical activity indicate a sample of frail and fatigued OCSs, also described characteristics for this target group in previous studies [19,36]. The high prevalence of frailty in OCSs might lead to concerns and further to their poor life satisfaction experience.…”
Section: New Findings and Their Meaningsupporting
confidence: 80%
“…Body aches are likely to increase discomfort among elderly adults, which in turn can affect their daily activities and increase their negative emotions. Some studies show that there is a relationship between the degree of physical pain and depression in the elderly [22]. However, others are indicating no correlation in such relationship as high tolerance of pain, reduced sensitivity to pain, and elderly people subjectively thinking the pain is the natural result of the age could also be the possibilities [23].…”
Section: Discussionmentioning
confidence: 99%
“…Women showed a higher level of fatigue compared to men. 13,21 Also, the scores obtained in the Lawton scale (IADL), as well as the results of the FACIT-F functional assessment, were analyzed. The research showed that patients with better performance in terms of instrumental activities assessed more positively their physical condition and functioning in everyday life, while presenting a lower level of fatigue and a satisfactory general functional performance.…”
Section: Discussionmentioning
confidence: 99%